Isospora araponga sp. n. (Apicomplexa: Eimeriidae), a new species of Isospora Schneider from a bare-throated bellbird, Procnias nudicollis (Vieillot, 1817) (Passeriformes: Cotingidae) from Brazil - Markéta Dolezalová; Jordi Torres; Hugo Fernández; David Modrý (Memorias do Instituto Oswaldo Cruz, 2004)
Faecal samples from a couple of bare-throated bellbirds Procnias nudicollis imported from Brazil to Barcelona Zoo contained oocysts of Isospora araponga n. sp. Sporulated oocysts were subspherical to broadly ellipsoidal, 19.5 (17-22) × 15.5 (14-16.5) µm, shape index (length:width ratio) 1.26 (1.13-1.38) with smooth and colourless bilayered wall, about 1 µm thick, and with varying number (1-3) of polar granule, but without a micropyle or residuum. The sporocysts were ellipsoidal, slightly asymmetric, 12.5 (12-13) × 8.5 (7.5-9) µm with barely visible Stieda body and indistinguishable substieda body. Sporozoites were elongated, possessing smooth surface and two distinct refractile bodies.